PEMANFAATAN APLIKASI PLICKERS DALAM EVALUASI PEMBELAJARAN IPS TERPADU DI SMP NEGERI 2 BOLAANG MONGONDOW UTARA SULAWESI UTARA - Nusi, Sepriyanto; Popoi, Irina; Bahsoan, Agil; Mahmud, Melizubaida; Gani, Imam Prawiranegara (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to determine the process of using the Plickers Application in evaluating Integrated Social Science Learning at SMP Negeri 2 Bolaang Mongondow Utara, North Sulawesi. The method used in this research is a qualitative approach with descriptive method. By interviewing the school principal, head of curriculum, head of facilities and infrastructure, social studies teacher and 4 class VIII students. The data collection techniques used observation, interviews and documentation, while the data analysis techniques used included data reduction, data display, and conclusion. The research findings indicate that the use of Plickers application in evaluating Integrated Social Science learning at SMP Negeri 2 North Bolaang Mongondow encompasses several stages, namely the preparation or planning stage, implementing the Plickers application in class, learning evaluation and student assessment results using the Plickers application. In addition, the use of Plickers application in evaluating learning in the classroom will make it easier and shorten the time during the evaluation process. Also, the application makes the evaluation more effective and efficient. Apart from that, this digital application-based assessment model helps students to not get bored easily and are enthusiastic about taking part in the evaluation. This condition is noticeable from several interviews conducted by researchers with several class VIII students. In the meantime, one of the supporting factors needed when carrying out learning evaluations using the Plickers application is the availability of facility and infrastructure at SMP Negeri 2 Bolaang Mongondow Utara. Another supporting factor includes the availability of adequate technological infrastructure such as projectors, computers and stable internet connections can support the use of the Plickers in learning evaluation. Thus, adequate facilities, equipment and infrastructure make it possible for teachers to easily access and use this application.